(untitled) (NAU Journal of Technology and Vocational Education, 2024)
The study was undertaken to determine the level of ICT competencies of Business studies teachers in junior secondary schools in Enugu East senatorial zone of Enugu state Nigeria. Two research questions guided the study and two null hypothesis were tested. Survey design was adopted and the population consisted of 352 NCE graduate teachers in junior secondary schools in the area. The entire population was used for the study. The instrument used was questionnaire with a 5 point rating scale containing 27 items in two sections. The instrument was validated by three experts, two in measurement and evaluation and one in computer science. The reliability of the instrument was determined using cronbach Alpha reliability formula forinternal consistency and reliability. Coefficients of 0.76 and 0.85 were obtained for the two sections. Data in respect of a research questions were analysed using mean and standard deviation while the hypotheses were tested using independent t-test (I tail, p-val = 0.05) on SPSS software. The two research questions showed that the ICT competency of teachers were moderate. All the two hypotheses tested showed that there were significant differences between the mean responses of the teachers (mean = 0.05), hence all the null hypotheses were rejected. The study revealed that teachers were not highly competent in ICT to enhance their teachings. Based on the finding of the study, it was recommended that government should organise workshops, seminars and conferences for secondary school teachers to enhance their ICT competencies and also grant study leave with pay to teachersto enable themembarkonICTtraining programmes.